Are Outcomes Following Crossed Lag-Screw Modified Lapidus Technique for Hallux Abductovalgus Comparable to Plate-Screw Fixation Technique? A Study of Costs, Radiographic and Patient Reported Outcomes. Issue 1 (January 2022) - Paranjape, Chinmay S.; Lalli, Trapper; Tennant, Joshua N.
Category: Bunion; Diabetes Introduction/Purpose: The modified Lapidus (ML) for tri-planar HAV correction is a powerful procedure for correcting hallux valgus (HV) and metatarsal rotation. We assessed implant costs, radiographs, and pre and postoperative patient reported outcome measures of Patient Reported Outcome Information System Physical Function (PROMIS-PF) Computerized Adaptive Test scores (CAT) at an average of 20.2 months followup. Methods: We examined patients retrospectively from January 2014 to December 2019. Pre and postoperative PROMIS-PF, radiographic parameters (intermetatarsal angle, IMA and HV angle, HVA), complications, and total surgical time were reviewed from the medical chart. Estimated surgical implants costs were obtained from manufacturers. Results: 83 patients underwent lag screw lapidus. All had radiographs, 71 had complete PROMIS-PF. Patients were a median age 55.80 (45.55, 53.85), 6.7% male, and 20% diabetic (median A1c 6.4%). Complications included 6.7% delayed wound healing, 13.3% painful hardware, 13.3% superficial infections. Others (7/83 or 8.4%) included complex regional pain syndrome in one, overcorrection in two, paresthesia in one and symptomatic nonunion in three. Preoperative angles were hallux valgus angle 33 (30, 40), IMA 15 (12, 16) which improved at final postoperative follow up to HVA 9 (5, 15) and IMA 7 (6, 9). PROMIS-PF was 43 (37, 52) preoperatively, 37 (31, 39) at six weeks, 46 (42, 51) at three months, and 49 (41, 53) at > 360 days. The drop in PROMIS- PF between preop and 6 weeks and the rise from 6 weeks to 3 months were significant. There was no difference between pre and postoperative PROMIS-PF. Implants averaged $140 USD. Conclusion: Patients achieved good radiographic correction of HV following ML by our technique. While physical function, measured by the PROMIS-PF, decreased in the acute postoperative period, it increased to near final levels by three months postoperatively. Low complication rate, low cost, and high patient postoperative functional expectations with excellent radiographic correction were demonstrated.